MENTORING MODEL AINUL YAKIN THERAPY ISLAMIC BOARDING SCHOOL IN IMPLEMENTING ISLAMIC VALUES IN THE COMMUNITIES OF KARANGTENGAH, TEPUS, GUNUNGKIDUL - Salman Alfarisi; KHONSA ROFIDAH (Program Studi Pengembangan Masyarakat Islam STID Mohammad Natsir, 2022)
Research purposes:To find out how the mentoring model carried out by the Ainul Yakin Islamic boarding school in instilling Islamic values ​​into the people of Krangtengah Hamlet, Tepus, Gunungkidul. Research Methods: Qualitative. The results of the study: The mentoring model carried out was categorized into four stages, namely First, Assistance by providing facilities to the community, in the form of providing a place, providing study materials through recitations held by the Islamic boarding school, activities for managing corpses and fostering ta'mir mosques. in Karangtengah Hamlet. Second, assistance through strengthening, namely by providing religious guidance to the community, involving the community to become employees of Islamic boarding schools, mutual cooperation and training. Third, assistance on the aspect of protection, Islamic boarding schools protect the community from the threat of the Plecit bank that ensnares residents. Fourth, the stage of support, implemented in the form of support for Islamic boarding schools in providing facilities and infrastructure for the community da'wah process.